Assessing the welfare of smallholder pigs in Vietnam using a pilot protocol - Sinh Dang-Xuan; Le Thi Thanh Huyen; Tu-Quynh Ha; Do Van Duc; Le Tien Dung; Han Anh Tuan; Unger, Fred; Doyle, Rebecca; Toribio, J.-A. (Springer, 2025)
Smallholder pig farms are an important feature of pork supply in Asia, and these farming approaches present unique management considerations. This survey was conducted to pilot a welfare assessment protocol and to investigate smallholder pig management and welfare at two sites in Vietnam, one with 55 farms raising predominantly indigenous pigs (the Da Bac site) and the other 55 farms raising predominantly non-indigenous pigs (the Lac Son site). Farmers at both sites kept small numbers of confined pigs, with more keeping sows in Da Bac and some keeping only grower pigs in Lac Son. Via an interview and pig observation, data on 18 welfare measures were recorded for adult pigs, suckling piglets and grower pigs. Pigs on > 90% of farms did not exhibit panting, tail biting, scouring, negative social behaviour, stereotypic behaviour, coughing or lameness demonstrating adequate welfare for these welfare measures. However, all pigs on > 50% of farms had restricted access to drinking water at both sites, and pigs often displayed fear of humans in the Da Bac site. The body condition of most pigs was thin or very thin among the sows on 31% of farms and among the grower pigs on 32% of farms. This pilot proved that the welfare assessment protocol is feasible and provided lessons for its future use in other low-to-middle income countries. It also found that low-cost interventions are urgently needed to address water access and undernutrition in order to improve the welfare of smallholder pigs and the production of these farms.